Hydrological and biogeochemical controls on Fe cycling at the Krabbenkreek supratidal/intertidal zone, the Netherlands: Why does the Fe pump sputter?. (5th April 2019) - Morera-Chavarría, Alejandra; Griffioen, Jasper; Chueca-García, Isabel; Faneca-Sánchez, Marta; Behrends, Thilo
Abstract: Frequent and unexplained iron enrichments have been localized in buried, Holocene, marine sediments in coastal areas. These buried sediments are nowadays often part of groundwater systems in densely populated deltas. Here, the Krabbenkreek intertidal/supratidal area in the Netherlands is considered as a present analogue for diagenetic processes in these near-shore sediments. We evaluate the role of tidally driven groundwater flow alternations on the transport and speciation of Fe in deep tidal sediments. This was achieved by examining geochemical sediment and porewater data in the context of 3-D geohydrological modelling results of the groundwater system. The Krabbenkreek area presents clear hydrologic and geochemical zonations across the supratidal/intertidal area. Due to the low hydraulic conductivity, groundwater flow and infiltration of rain water is limited in the mud-rich upper sediments of the supratidal flat. Despite tidal fluctuations of the hydraulic heads up to 1.5 m, the corresponding alternating groundwater flow is relatively minor in comparison to the net groundwater flow. Tidal variations in the groundwater force field alone did not lead to pronounced local enrichments in reactive Fe. Differences in reactive Fe contents in deep sediments can be related to textural differences, implying that no indications for local, diagenetic Fe enrichments were found in the sediments down to 5 m depth. Contents of FeS and amorphous Fe(III) are remarkably low indicating little current dynamics in Fe redox cycling in these deep sediments, while the porewater chemistry indicates that pyrite oxidation prevails. Long-term oxidation of pyrite is reflected by the presence of Fe(III) oxides in the high marsh sediments while pyrite still dominates in the middle marsh and the intertidal sediments. Absence of active Fe redox cycling can be attributed to low respiratory activity in the sediments. Previous studies reported that sedimentary organic matter in the vicinity of the investigated area can be predominately refractory, which can probably explain the low respiratory activity in the Krabbenkreek sediments. Graphical abstract: Image 1 Highlights: Minor tidal alternations in groundwater flow despite large groundwater head changes. Limited Fe cycling within buried estuarine sediments by low respiratory activity. Oxidation of deposited Fe sulphides is the prevailing transformation of reactive Fe.